2011
DOI: 10.1161/strokeaha.111.617415
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Glycemic Control Is Associated With the Functional Outcome in Acute Ischemic Stroke

Abstract: MD; for the FSR InvestigatorsBackground and Purpose-Diabetes mellitus is an established risk factor for stroke. However, it is uncertain whether prestroke glycemic control (PSGC) status affects clinical outcomes of acute ischemic stroke. The aim of this study was to elucidate the association between PSGC status and neurological or functional outcomes in patients with acute ischemic stroke. Methods-From the Fukuoka Stroke Registry (FSR), a multicenter stroke registry in Japan, 3627 patients with first-ever isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 32 publications
(23 reference statements)
12
133
7
Order By: Relevance
“…In the subgroup analysis, we determined that NDDM with single high HbA1c did not exhibit a definite correlation with a poor prognosis compared with non-DM. Several studies have indicated that high HbA1c at admission was an independent significant predictor of poor prognosis in ischemic stroke patients without a DM history 31,32 ; however, these studies did not exclude patients with in-hospital hyperglycemia. Thus, the results could not prove the relationships between single high HbA1c and stroke prognosis.…”
Section: August 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…In the subgroup analysis, we determined that NDDM with single high HbA1c did not exhibit a definite correlation with a poor prognosis compared with non-DM. Several studies have indicated that high HbA1c at admission was an independent significant predictor of poor prognosis in ischemic stroke patients without a DM history 31,32 ; however, these studies did not exclude patients with in-hospital hyperglycemia. Thus, the results could not prove the relationships between single high HbA1c and stroke prognosis.…”
Section: August 2016mentioning
confidence: 99%
“…Second, the current cutoff point of HbA1c criteria for DM diagnosis was based on the correlation between the HbA1c level and the risk of developing diabetic retinopathy that represent small vessel disease 36,37 ; however, it was not used to predict the prognosis of ischemic stroke patients, which mostly represent large vessel disease or cardioembolism disease. Although some research has demonstrated that an increased HbA1c at admission was an independent significant predictor for poor prognosis in ischemic stroke patients, 31,32 it is not clear which cutoff point for HbA1c is best fit to predict the prognosis regarding the prevention of a second stroke. Finally, there are racial and ethnic differences regarding HbA1c levels, 38 and the HbA1c levels tend to be increased in Asians compared with whites with impaired glucose tolerance.…”
Section: August 2016mentioning
confidence: 99%
“…A second common principle is that certain stroke comorbidities are strongly associated with poor neurological outcome. In particular, clinical studies have shown that diabetes increases the risk of ischemic stroke and is associated with slower or poorer recovery of function/independence (Clavier et al, 1994;Jorgensen et al, 1994;Hankey et al, 2007;Kamouchi et al, 2011), even when adjusting for confounding factors such as age and stroke severity (Wei et al, 2010).…”
Section: Effect Of Diabetes On Stroke Recoverymentioning
confidence: 99%
“…A recent study by Li et al, is one of the few studies systematically investigating the role of HbA1c on stroke outcome, regardless of a prestroke diagnosis of DM; their results show that elevated HbA1c level relates to stroke severity and poor prognosis in the whole study population; however, only patients with brainstem infarction were included in this study. 6,7 In a study conducted in Faisalabad in 2006, the frequency of raised HbA1c was 56.4% in patients presenting with ischemic stroke. 8 But another study conducted , the frequency of raised HbA1c was 13.2% in patients presenting with ischemic stroke.…”
Section: -4mentioning
confidence: 99%